Grasping product pragmatics: A case with internet on TV - Koca, Aylin; Funk, Mathias; Karapanos, Evangelos; Rozinat, Anne; Van Der Gaarden, Nico (My University, 2008)
With the emergence of highly interactive products in the domestic space, consumer electronics brands are facing an increasing challenge in predicting the way their products are being used and experienced. Unforeseen experiences relating to functional, emotional and social/contextual aspects of product use lead to a large and increasing share of field complaints that cannot be attributed to a violation of products' specifications. In a project called Soft Reliability, we are trying to develop a product evaluation ecology that enables the anticipation of product use by gathering behavioral and attitudinal data early in the product development process, through longitudinal field studies with working prototypes. This paper introduces a novel framework for behavioral and attitudinal data collection and analysis. The framework enables instrumentation that relies on the event-based experience sampling method, and as such deploys an analysis methodology that includes process mining techniques for the analysis of usage patterns, multivariate techniques for the analysis of longitudinal attitudinal data, and product quality analysis techniques for the analysis of combined information. We illustrate the value and applicability of this framework in practice, through the findings of an ongoing project concerning the conceptualization of an innovative Internet on TV product, which is being conducted in collaboration with Philips, a multi-national consumer electronics company.
Keywords: Product conceptualization; Product usage logs; Soft reliability; Subjective user feedback; User experience evaluation